Strength response characteristics and coupling support of deep roadway in soft rock masses. Issue 1 (1st January 2017) - Jun-jie, Huang; Ya-guang, Qin; Shuang, Zhao; Wei, Wang; Lei, Wen
Abstract: Monitoring analysis was performed for the deformation characteristics of a deep roadway in soft rock masses in a certain mine by the convergence instrument. It was indicated that shotcrete and bolt support for the surrounding rock deformation under forces produced a poor effect so that a shotcrete rockbolt mesh coupling support pattern was put forward and four coupling support schemes were designed to carry out field monitoring for surrounding rock deformations on the basis of above schemes. According to the research, we could summarize as follows. Firstly, when load in floor strata reached a certain value, shear failure took place on the edge of floor; then, with the continuous increase of such a load, shear zones were subsequently expanded and connected together into one big region; at that time, as the load on floor strata had been up to its limit, the floor could be settled sharply as long as this load went up slightly so that the uplift of rock mass gave rise to floor heave. Secondly, bearing capacity of floor rocks was dependent on the average binding force, internal friction angle and unit weight of floor rocks as well as the concentrated stress action width of lateral wall and the average pressure value borne by the roadway floor. Thirdly, after the shotcrete rockbolt mesh coupling support was adopted, two-sided displacement dropped 80% and above, roof subsidence decreased more than 70% and the capacity of floor heave falls by over 90%; as a result, stability of the roadway could be significantly improved.